Expression of IL-33 Receptor Is Significantly Up-Regulated in B Cells During Pregnancy and in the Acute Phase of Preterm Birth in Mice - Valeff, Natalin; Juriol, Lorena; Quadrana, Florencia; Muzzio, Damián Oscar; Zygmunt, Marek; Quiroga, Maria Florencia; Ventimiglia, María Silvia; Jensen, Federico (Frontiers in Immunology, 2020)
Interleukin-33 (IL-33) is a mucosal alarmin belonging to the IL-1 cytokine family and is now recognized to have a key role in innate and adaptive immunity, contributing to tissue homeostasis and response to environmental stresses. In addition, IL-33 has also been shown to work as a positive regulator that initiates and maintains a Th2 immune response. In the context of pregnancy, it has been recently demonstrated that upon certain stress conditions, such as an infection induced inflammation, IL-33 is released from the uterine mucosa and triggers decidual B cells to produce anti-inflammatory molecules, which in turn restore immune homeostasis and prevents the development of preterm birth. In this study we therefore performed a detailed characterization of IL-33 receptor (Il1rl1 or ST2) expression in B cells during normal pregnancy, as well as in a mouse model of preterm birth. We observed that splenic B cells significantly up-regulate the expression of Il1rl1 during pregnancy and identified the B1 B cell population as the main ST2-expressing B cell subset. A further kinetic analysis showed that percentages of ST2-expressing B1 B cells are significantly augmented on days 12 and 14 of pregnancy, both in the spleen and peritoneal cavity of pregnant mice, and then drop toward the end of pregnancy to the levels observed in non-pregnant animals. Furthermore, using a mouse model of LPS-induced preterm birth, we demonstrated that not only are the percentages of ST2-expressing B1 B cells significantly enlarged in the spleen during the acute phase of preterm birth, but decidual B cells also significantly up-regulate ST2 expression as compared to term-pregnant mice. Overall, our results suggest a functional role of ST2 expression in B cells during pregnancy and reinforce the importance of the IL-33/ST2 axis in B cells as a critical mechanism to control inflammation-induced preterm birth.